Pembangunan pertanian di Desa Wonocoyo Kecamatan Panggul Kabupaten Trenggalek - Tanjung, Ahmad Hartono; Muhammad, Faqih Fawwaz; Talitha, Firzanah Adya; Aditama, Muri; Asna, Zaki Millati (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Development does not only pursue growth but also needs to pay attention to environmental aspects so that there is no exploitation of natural resources owned to realize prosperity. Development that only pursues growth and does not pay attention to environmental aspects has a negative impact on the environment and on the sustainability of life. Findings: Increasing income and increasing income equality can change domestic demand patterns, increasing community income and increasing population, which will shift demand from agricultural goods (food) to non-agricultural goods (industry and services). Changes in demand patterns will encourage a transformation of the production structure. The transformation of the production structure is marked by a decrease in the relative share of GDP in the agricultural sector. Methods: This study uses a case study with data sources through primary and secondary data with support from the interview technique used. Conclusion: The Wonocoyo Village Government can improve extension activities to be more effective and efficient because farmers still rely on techniques from their ancestors, and it is hoped that the Wonocoyo Village Government can strive to convert livestock waste into biogas by using the Submarine Bioreactor Tube to utilize livestock waste into more useful results.